My mini book of vegetables (Say Publishing Karachi, 2011)
This colorful mini book introduces young readers to a variety of vegetables. With simple text and engaging illustrations, children will learn the names of different vegetables, their colors, and their shapes. From crunchy carrots to leafy spinach, this book sparks curiosity and encourages healthy eating habits. Perfect for preschoolers and early elementary students, this mini book is a delightful way to explore the wonderful world of vegetables.